A execução dos Convênios de Fundo de Infraestrutura (CT- INFRA) celebrados entre a Financiadora de Estudos e Projetos (FINEP) e a Universidade Federal do Espírito Santo (UFES) sob a ótica da eficácia - Souza, Juliano Azevedo de (2016)
The present work deals with the execution of the Infrastructure Fund Agreements (CT-INFRAs) concluded between the Studies and Projects Funder (FINEP) and the Federal University of Espírito Santo (UFES) in the period of 2004-2010 from the perspective of efficacy. The central question is to verify if the institutions are able to execute the CT-INFRAs within the agreed period of time with the FINEP. The study was conducted at the UFES. The starting point was to question the FINEP, via information portal, data from all the institutions that participated in the agreements in the referred period. Such data were related to the term of execution of the agreement, time destined to release the second installment and percentage spent of the total value. When comparing the data, it was concluded that rarely can an institution execute the agreements within the agreed three-year time frame. In addition, questionnaires were applied to project coordinators, the FINEP, the University City Hall (PU) and the Espírito Santense Foundation of Technology (FEST), to verify the execution of the agreements, relative to the UFES. In parallel, a focus group was applied, together with the PU and the FEST to build the Current Reality Tree (ARA), with the objective of finding the root causes for poor performance of agreements. The results obtained through the analysis point to the need for improvement in planning, relative to the management of the agreements. The Script Lattes tool was also used to investigate the production of articles from each scientific team of the CT-INFRAs. When relating the scientific production of each team with the articles produced by the UFES, it was concluded that the CT-INFRAs can significantly impact production of articles and contribute to the improvement of postgraduate programs. Lastly, a proposal for improvement was presented with the intent that the agreements could be managed more effectively